Enhanced Cycling Stability of Macroporous Bulk Antimony‐Based Sodium‐Ion Battery Anodes Enabled through Active/Inactive Composites. Issue 31 (1st October 2018) - Ruiz, Olivia; Cochrane, Mark; Li, Manni; Yan, Yan; Ma, Ke; Fu, Jintao; Wang, Zeyu; Tolbert, Sarah H.; Shenoy, Vivek B.; Detsi, Eric
Abstract: Engineering strategies based on "nanostructuring" and "active/inactive composites" are commonly used separately to improve the performance of alkali‐ion battery electrodes. Here, these two strategies are merged to further enhance the performance of alloy‐type alkali‐ion battery anodes. Specifically, macroporous antimony (Sb)/magnesium fluoride (MgF2 ) active/inactive composite material is used as a high‐performance Na‐ion battery anode. The porous Sb phase with pore size in the sub‐micrometer range acts as the electrochemically active component and the electrochemically inactive dense MgF2 phase acts as a mechanical buffer. Na‐ion battery anodes made of porous Sb/MgF2 active/inactive composites are reversibly sodiated for over 300 cycles, delivering a capacity of ≈551 mAh g −1 after 300 cycles at a C‐rate of C/2. This performance is remarkable because the porous Sb/MgF2 composite is not made of mesoporous structures. Furthermore, the cycling longevity of this porous Sb/MgF2 composite outperforms the common nanostructured Sb‐based Na‐ion battery anode materials. This good performance is attributed to the "porous active/inactive" configuration, where the dense inactive mechanical buffer phase absorbs part of the phase transformation‐induced stresses, while porosity in the active phase helps to accommodate the phase transformation induced volume expansions and electrolyte transfer into the bulk of this composite. Abstract : This work reports on a high‐performance Na‐ion battery anode consisting of macroporous Sb/MgF2 active/inactive composites in which dense MgF2 (blue in figure) acts as an electrochemically inert mechanical buffer that absorbs sodiation‐induced volume expansions in the macroporous Sb (red in figure), the active phase for Na storage.